The European Union as a global counter-terrorism actor - Kaunert, Christian (European security and justice critiques, 2022)
"This significant book provides a comprehensive analysis of the global dimension of European Union (EU) counter-terrorism. It focuses on the growth of the EU as a global counter-terrorism actor, from it having almost no role in 2001 to becoming a significantly greater force in recent years. Analysing one of the most important policy areas of European integration, authors Christian Kaunert, Alex MacKenzie and Sarah Leonard consider the key question of why the EU may have become a global actor in counter-terrorism. The authors then develop a unique theoretical approach in the form of actorness and collective securitization, which analyses the EU's evolution as a counter-terrorism actor in different case studies, such as counter-terrorism in the transatlantic relationship, North Africa, the Middle East and South Asia. Overall, this book highlights that the EU is, in fact, becoming a counter-terrorism actor of growing importance and with an ever-diversifying number of policy options available. Addressing topical matters, this book will be a key resource for scholars, researchers and students in fields such as European studies, international relations, political science and governance. It will also attract the attention of practitioners, politicians, non-governmental and civil society organisations"--